A Contrastive Analysis Of Suffixes Between English and Batak Simalungun Language - Putri Raisah Sihotang; Arni Wulandari Sinaga; Renita Clara Siahaan; Anita Sitanggang (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This study aims to describe the most common types of English and Simalungun suffixes found in narrative texts and find similarities and differences. The author uses descriptive qualitative research to obtain valid data. After investigating the data, the writer found several findings based on the analysis of the types of English suffixes and simalungu n.English suffixes have four types; nominal, verbal, adjective and adverbial suffixes. There are one hundred and three suffixes that are categorized as suffixes in simalungun language. In contrast, there are one hundred and seventy-four endings which are categorized as endings in English. The writer finds differences and similarities between the two; it depends on their breed. In English suffixes and Simalungun languages suffixes have adverbial suffixes. The same type of suffixes in English and Simalungun are that both have suffixes that form nouns, verbs and adjectives.